PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN RISIKO SEBAGAI VARIABEL MEDIASI - Hasna Nur Afifah; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2021)
This study aims to provide a deeper explanation regarding the Effect of of Corporate Social Responsibility on Corporate Financial Performance with Risk as a Mediating Variable. The population in this study are companies in the few sectors in natural resource industry listed on the Indonesia Stock Exchange (IDX) from 2011 to 2019, especially in mining, agriculture and basic industries’s sectors. This study uses secondary data and purposive sampling method as a method of selecting samples. Also, this study uses PLS (Partial Least Square) analysis as model data analysis. The results showed that CSR has a positive effect on CFP, CSR has a positive effect on company risk and company risk has an effect as a mediating variable between CSR and CFP.